2019
DOI: 10.4414/smw.2019.20171
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implants in single-sided deafness – clinical results of a Swiss multicentre study

Abstract: AIM OF THE STUDY: The aim of this multicentre, prospective, open, nonrandomised clinical trial was to demonstrate the clinical efficiency and outcomes of cochlear implants (CIs) in adult patients with post-lingual single-sided deafness (SSD).METHODS: A group of five left and five right SSD participants were investigated with various clinical tests and questionnaires before and 12 months after CI activation. Changes in hearing thresholds, speech understanding in noise, sound localisation, tinnitus (Tinnitus Han… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 58 publications
6
23
0
4
Order By: Relevance
“…For the first time in 2008, Van de Heyning et al [ 5 ] reported a significant decrease in tinnitus distress (TQ) and tinnitus loudness (Visual Analogue Scale (VAS) score) following cochlear implantation in unilaterally deaf patients suffering from incapacitating tinnitus. Later, others reported beneficial results of electrical stimulation by cochlear implantation on tinnitus as well [ 17 , 20 , 31 , 38 , 39 ]. An important issue to be mentioned is the absence of a minimum level of tinnitus distress to be eligible for inclusion in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the first time in 2008, Van de Heyning et al [ 5 ] reported a significant decrease in tinnitus distress (TQ) and tinnitus loudness (Visual Analogue Scale (VAS) score) following cochlear implantation in unilaterally deaf patients suffering from incapacitating tinnitus. Later, others reported beneficial results of electrical stimulation by cochlear implantation on tinnitus as well [ 17 , 20 , 31 , 38 , 39 ]. An important issue to be mentioned is the absence of a minimum level of tinnitus distress to be eligible for inclusion in our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the proportion of patients that opted for BCD or CROS after the trial period was not mentioned, and no objective outcomes of hearing performance were published from these satisfied patients. Likewise, SSD patients were offered a CI in a Swiss study if they had unsatisfactory benefit from a trial with CROS or BCD: forty-four of 54 study patients did not proceed to cochlear implantation [ 39 ]. Unfortunately, there were no results available from those patients who opted for BCD or CROS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…En 2019, une étude multicentrique suisse a été publiée avec une analyse de la performance auditive détaillée de 10 patients implantés avec surdité unilatérale. 13 Elle a montré une amélioration significative de la compréhension dans le bruit, surtout dans les situations les plus difficiles pour le patient. On retrouvait aussi un gain quand l'oreille saine est masquée par du bruit, ce qui n'est pas possible avec des systèmes pseudo-stéréophoniques.…”
Section: Figunclassified
“…11,14 Tous ces gains, mesurés et objectivables, se reflètent dans une amélioration substantielle de la qualité de la vie globale 13. Il est important de savoir que la performance auditive avec un implant cochléaire pour surdité unilatérale reste inférieure par rapport à celle d'un patient avec une audition normale.…”
unclassified